Cosmetic Comparison Between the Modified Uchida Method and the Mustarde Method for Blepharophimosis–Ptosis–Epicanthus Inversus Syndrome. Issue 5 (November 2015) - Yamaguchi, Kazuaki; Imai, Keisuke; Fujimoto, Takuya; Takahashi, Makoto; Maruyama, Yoko
Abstract : Purpose: Blepharophimosis–ptosis–epicanthus inversus syndrome (BPES) is a rare, congenital, surgically challenging disease. We undertook an objective, functional, and cosmetic comparison between the modified Uchida procedure and the Mustarde procedure on Asian patients with BPES. Design: This is a retrospective, comparative, interventional case series with the description of 2 surgical techniques. Participants: Twenty consecutive Japanese patients with BPES were studied. Methods: The patients were assigned to either the modified Uchida or the Mustarde procedure on the basis of preoperative intercanthal distance (ICD) ratio (ICD/palpebral fissure width). Intercanthal distance and margin reflex distance were measured from photographs before and after surgery. Classifications were made according to epicanthal fold score and cosmetic score using a visual analog scale (VAS). Main Outcome Measures: The main outcome measures were postoperative improvement in ICD ratio and the VAS. Results: Of the 20 patients, 5 underwent the modified Uchida procedure and the other 15 underwent the Mustarde procedure. The preoperative median ICD ratio was 2.0 (range, 1.9–2.5) and 2.5 (range, 2.0–3.4) for the modified Uchida and Mustarde procedures, respectively, and decreased to 1.5 (range, 1.5–1.7) and 1.6 (range, 1.5–1.8) postoperatively. The mean ICD reduction rate was 35.7% (SD, 1.0%) in the Mustarde group and 22.1% (SD, 1.3%) in the modified Uchida group ( P < 0.001). The mean VAS for the modified Uchida and Mustarde procedures was 5.9 (SD, 1.3) and 2.8 (SD, 1.1), respectively, which was statistically significant ( P = 0.0166). Conclusions: Both the modified Uchida and Mustarde procedures could effectively shorten the ICD; however, cosmetic results were significantly superior using the modified Uchida method.